LGG-57. SIGNALLING MECHANISMS IN PAEDIATRIC LOW-GRADE GLIOMA. (4th December 2020) - Patel, Ankit; Jones, Tania; Woodward, Lewis; Dokal, Arran; Rajeeve, Vinothini; Cutillas, Pedro; Stone, Thomas; Jacques, Thomas; Sheer, Denise
Abstract: Paediatric low-grade gliomas (pLGGs) constitute the largest group of childhood CNS tumours. They often cause significant disability and morbidity, despite their indolent growth and the good survival rate of patients. The most common genetic alterations in these tumours, KIAA1549:BRAF fusion and BRAF V600E mutation, lead to abnormal activation of MAPK signalling. The central role of this pathway in pLGG development is emphasized by the occasional presence of other MAPK-activating alterations such as RTK mutations. It is not known how these different aberrations can induce the variety of clinical phenotypes seen in pLGG. Here, we compared pilocytic astrocytomas (PAs) containing the KIAA1549:BRAF fusion with glioneuronal tumours (GNTs) containing the BRAF V600E mutation, to identify differentially activated downstream targets of the MAPK pathway. Liquid chromatography tandem mass spectrometry (LC-MS/MS) was used as a multi-proteomic approach. Kinase Set Enrichment Analysis (KSEA) using PhosphositePlus and NetworkIN was used to determine relative enrichment of kinase activity in the tumours compared to healthy control brain tissue. Significant similarities and differences were found in the two tumour types. For example, more robust MAPK activation was found in the GNTs than in PAs. However, while PI3K/AKT1/mTOR signalling was active in both PAs and GNTs, there was statistically higher activation in the PAs. In both tumour types, there was significant reduction in casein kinase 2 activity, which likely affects nuclear translocation of ERK and, in turn, alters the range of its phosphorylated substrates. We will present these data together with transcriptomics to further characterise the downstream targets of these genetic alterations.